A model for cyclotron resonance scattering features - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Aims. We study the physics of cyclotron line formation in the high-energy spectra of accreting X-ray pulsars. In particular, we link numerical predictions for the line profiles to results from observational data analysis. Therefore, first we investigate the theoretical predictions and the significance of our model parameters, and second we aim at the development of a model to fit cyclotron lines in observational data.Methods. Simulations were performed using Monte Carlo methods. The data were extracted with HEADAS 6.1.1 and INTEGRAL OSA 5.1. A convolution model for the cyclotron line shapes was implemented for the XSPEC spectral analysis software package and for data packages compatible with XSPEC local models.Results. We predict the shapes of cyclotron lines for different prescribed physical settings. The calculations assume that the line-forming region is a low-density electron plasma, which is of cylindrical or slab geometry and which is exposed to a uniform, sub-critical magnetic field. We investigate the dependence of the shape of the fundamental line on angle, geometry, optical depth and temperature. We also discuss variations of the line ratios for non-uniform magnetic fields. We have developed a new convolution and interpolation model to simulate line features regardless of any a priori assumed shape of the neutron star continuum. Fitting RXTE and INTEGRAL data of the accreting X-ray pulsar V0332+ 53 with this model gives a qualitative description of the data. Strong emission wings of the fundamental cyclotron feature as predicted by internally irradiated plasma geometries are in principle observable by todays instruments but are not formed in V0332+ 53, hinting at a bottom illuminated slab geometry for line formation.
Keywords: X-rays : binaries; stars : neutron; accretion; accretion disks; magnetic fields; line : formation; methods : numerical